Unveiling Regional Disparities in Makhana Farming Practices: A Multidimensional Analysis from Bihar - Kumar Sonu,; Kaushal Kumar Jha, (Indian Journal of Extension Education, 2025)
Makhana (Euryale ferox) cultivation in Bihar accounts for 85% of India’s total production of Makhana, exhibiting pronounced regional disparities driven by agro-ecological, socio-economic, and institutional factors. This study compares traditional (Darbhanga/Madhubani) and emerging (Purnea/Katihar) Makhana-growing zones to elucidate differences in farming practices, resource endowments, and socio-behavioural attributes. In a comparative cross-sectional design, 120 Makhana growers (60 per region) were surveyed using a structured interview schedule covering landholding size, income level, training, age, education level, perception, knowledge and attitude level of farmers. Mann-Whitney U tests (α = 0.05) examined univariate regional differences; Multiple Correspondence Analysis and permutation testing (B = 999) assessed multidimensional separation and statistical significance of regional groupings. Univariate analysis revealed significant regional differences in landholding size, larger in traditional zones, perception scores higher in emerging zones, and income level. MCA showed robust grouping: the first two dimensions captured 49.38% of total variance. Though specific socio-economic and attitudinal factors appear similar, multidimensional profiling uncovers clear structural differences between traditional and emerging Makhana regions. These findings emphasize the need for region-tailored extension strategies, input support, and market interventions to foster equitable growth and resilience in Bihar’s Makhana sector.